Penerapan Model Polytomous Item Response Theory untuk Mengevaluasi Skala Student's Perception Of Assessment Questionnaire - Yusuf Hadi Yudha (Jurnal Ilmiah Psikologi MIND SET, 2010)
The aims of this study were to evaluate reliability and validity of the Student's Perception of Assessment Questionnaire (SPAQ), to evaluate and refine the instrument to improve its capacity as a measure through IRT modelling, to detect Differential Item Functioning (DIF), to evaluate students' perception on assessment, and to evaluate gender-based, grade-based, class program-based, school location-based, and school status-based differences in students' perceptions. Results showed that the validity and reliability coefficients revealed that the SPAQ was suitable for assessing students' perceptions on five assessment dimensions : Congruence With Planned Learning, Authenticity, Student Counsultation, Transparency, and Diversity. For the IRT models applied, only Generalized Partial Credit Model shows that 30 items of the SPAQ scale fit to the data. There are six items show DIF in two categories: Item 14, 17, 18, 21, 24, dan 25. The average scale-item mean values for all the scales were less than 3.0, which indicates a need to address these dimensions of assessment at classroom level. The perceptions of students grouped on the basis of gender, of grade level, of class program, of school location and of school status groups were comparable, but on the basis of school location groups were statistically significantly different for each sub scale. Specifically how a student thinks about their assessment will influence their response.